Pengaruh Perhatian Orang Tua Terhadap Perkembangan Moral Anak Usia Dini Di TK Rejo Asri - Nisa, Uswatun; Cahyo, Edo Dwi (Institut Agama Islam Negeri Metro, 2023)
Moral development in children is the process of children learning about moral and ethical values, therefore the influence of parents' attention on children will affect their moral development. The purpose of this study was to determine the effect of parental attention on the moral development of early childhood. The type of research conducted at Kindergarten Rejo Asri in this study was qualitative with a case study approach. As for data collection techniques using interviews, observation, and document analysis. And to test the validity using source and technique triangulation. Based on the results of research conducted at Perintis Rejo Asri Kindergarten, it can be concluded that children who experience a lack of parental attention result in children's moral development. Children who get enough attention will have a big impact on the character and moral values that children have in the future. Therefore parents are the main caregivers and role models for their children, and they also need to pay adequate attention to the moral development of their children by providing good values, providing proper supervision, and modeling good behavior consistently.